Cardiovascular Risk and Atherosclerosis Progression in Hypertensive Persons Treated to Blood Pressure Targets. Issue 6 (December 2019) - Gronewold, Janine; Kropp, Rene; Lehmann, Nils; Stang, Andreas; Mahabadi, Amir A.; Kälsch, Hagen; Weimar, Christian; Dichgans, Martin; Budde, Thomas; Moebus, Susanne; Jöckel, Karl-Heinz; Erbel, Raimund; et al.
Abstract : Arterial hypertension promotes atherosclerosis and cardiovascular events. We evaluated how cardiovascular risk and atherosclerosis progression are associated with blood pressure, antihypertensive treatment, and treatment efficacy. In 3555 participants of the population-based Heinz Nixdorf Recall study without previous cardiovascular disease (mean±SD; age, 58.9±7.6 years, 46.9% men), we analyzed associations of baseline antihypertensive treatment efficacy (normotension without antihypertensives, normotension with antihypertensives, hypertension without antihypertensives, hypertension with antihypertensives, based on 140/90 mmHg cutoffs) with incident coronary artery calcification (CAC) and CAC progression during 5-year-follow-up and with incident cardiovascular events during 13.5-year-follow-up. We further evaluated associations of incident arterial hypertension and efficacy of new antihypertensive treatment at the 5-year-follow-up with subsequent cardiovascular events. At baseline, 1706 participants had normotension without antihypertensives, 553 normotension with antihypertensives, 786 hypertension without antihypertensives, and 510 hypertension with antihypertensives. Six hundred forty-seven participants experienced rapid CAC progression. One hundred seven, 132, and 249 had incident stroke, coronary event, and cardiovascular event, respectively. Compared with normotensives without antihypertensives, normotensives with antihypertensives had an elevated stroke (hazard ratio, 2.33 [95% CI, 1.19–4.55]), coronary (2.04 [95% CI, 1.20–3.45]), and cardiovascular (2.23 [95% CI, 1.48–3.36]) risk, and increased baseline CAC, but not increased CAC progression. Participants without hypertension at baseline, who were newly hypertensive but achieved normotension with antihypertensives at the 5-year-follow-up, again exhibited elevated stroke (4.80 [95% CI, 1.38–16.70]) and cardiovascular (2.99 [95% CI, 1.25–7.16]) risk, whereas coronary risk was less elevated (2.24 [95% CI, 0.70–7.18]). Normotensives with antihypertensives have an elevated cardiovascular risk. They are characterized by elevated baseline CAC but show no signs of increased CAC progression. Abstract : Supplemental Digital Content is available in the text.